To evaluate the algebraic expression 13a + 9c for a = 165 and c = 467, we substitute the given values into the expression:
13(165) + 9(467)
Multiplying:
2145 + 4203
Adding:
6348
Therefore, the total revenue for a = 165 and c = 467 is $6348.
The Center for Science and Industry sells adult tickets for $13 and children's tickets for $9. The expression 13a +9c represents the total revenue from selling a adult tickets and c children's tickets. Evaluate the algebraic expression 13a + 9c for a = 165 and c = 467.
The total revenue for a = 165 and c = 467 is what? simplify the result
13 answers
The width of a rectangle is w yards and the length of the rectangle is (6w - 7) yards. The perimeter of the rectangle is given by the algebraic expression 2w + 2(6w - 7). Simplify the algebraic expression 2w+ 2( 6w - 7) and determine the perimeter of a rectangle whose width w is 2 yards.
Simplify the algebraic expression 2w+ 2( 6w - 7)
2w+ 2( 6w - 7) = [ ]
Simplify the algebraic expression 2w+ 2( 6w - 7)
2w+ 2( 6w - 7) = [ ]
To simplify the algebraic expression 2w + 2(6w - 7), we follow the order of operations, which states that we should perform operations within parentheses first:
2w + 2(6w - 7) = 2w + 12w - 14
Next, we can combine like terms:
= (2w + 12w) - 14
= 14w - 14
Therefore, the simplified algebraic expression 2w + 2(6w - 7) is 14w - 14.
To determine the perimeter of a rectangle whose width w is 2 yards, we substitute the value into the expression:
Perimeter = 14w - 14
Perimeter = 14(2) - 14
Perimeter = 28 - 14
Perimeter = 14
Therefore, the perimeter of the rectangle with a width of 2 yards is 14 yards.
2w + 2(6w - 7) = 2w + 12w - 14
Next, we can combine like terms:
= (2w + 12w) - 14
= 14w - 14
Therefore, the simplified algebraic expression 2w + 2(6w - 7) is 14w - 14.
To determine the perimeter of a rectangle whose width w is 2 yards, we substitute the value into the expression:
Perimeter = 14w - 14
Perimeter = 14(2) - 14
Perimeter = 28 - 14
Perimeter = 14
Therefore, the perimeter of the rectangle with a width of 2 yards is 14 yards.
2w + 2 (6w - 7 ) =
To simplify the expression 2w + 2(6w - 7), we need to use the distributive property:
2w + 2(6w - 7) = 2w + 2 * 6w - 2 * 7
Now, we can simplify by performing the multiplication:
= 2w + 12w - 14
Next, we can combine like terms:
= 14w - 14
Therefore, the simplified expression for 2w + 2(6w - 7) is 14w - 14.
2w + 2(6w - 7) = 2w + 2 * 6w - 2 * 7
Now, we can simplify by performing the multiplication:
= 2w + 12w - 14
Next, we can combine like terms:
= 14w - 14
Therefore, the simplified expression for 2w + 2(6w - 7) is 14w - 14.
What is the perimeter of the rectangle whose width w is 2 yards?
[ ] yards
[ ] yards
To find the perimeter of the rectangle when the width w is 2 yards, we substitute w = 2 into the expression we simplified earlier:
Perimeter = 14w - 14
Plugging in w = 2:
Perimeter = 14(2) - 14
Perimeter = 28 - 14
Perimeter = 14 yards
Therefore, the perimeter of the rectangle when the width is 2 yards is 14 yards.
Perimeter = 14w - 14
Plugging in w = 2:
Perimeter = 14(2) - 14
Perimeter = 28 - 14
Perimeter = 14 yards
Therefore, the perimeter of the rectangle when the width is 2 yards is 14 yards.
Use the distributive property to remove the parentheses.
- (8x - 8y)
- (8x - 8y) = [ ]
- (8x - 8y)
- (8x - 8y) = [ ]
To use the distributive property to remove the parentheses in - (8x - 8y), we need to distribute the negative sign to each term inside the parentheses:
- (8x - 8y) = -8x + 8y
Therefore, when we remove the parentheses using the distributive property, - (8x - 8y) simplifies to -8x + 8y.
- (8x - 8y) = -8x + 8y
Therefore, when we remove the parentheses using the distributive property, - (8x - 8y) simplifies to -8x + 8y.
Simplify each expression by combining like terms.
-8(n - 4) + 2 ( n + 1)
-8(n - 4) + 2 ( n + 1) = [ ]
-8(n - 4) + 2 ( n + 1)
-8(n - 4) + 2 ( n + 1) = [ ]
To simplify the expression -8(n - 4) + 2(n + 1), we use the distributive property and then combine like terms:
-8(n - 4) + 2(n + 1) = -8n + 32 + 2n + 2
Now we can combine like terms:
= (-8n + 2n) + (32 + 2)
Simplifying further:
= -6n + 34
Therefore, -8(n - 4) + 2(n + 1) simplifies to -6n + 34.
-8(n - 4) + 2(n + 1) = -8n + 32 + 2n + 2
Now we can combine like terms:
= (-8n + 2n) + (32 + 2)
Simplifying further:
= -6n + 34
Therefore, -8(n - 4) + 2(n + 1) simplifies to -6n + 34.
Decide whether the statement is an example of the commutative, associative, identity, inverse, or distributive property.
- 15 + (7 + 6) = ( -15 + 7) + 6
The statement is an example of which of the following properties?
Identity
Associative
Inverse
Communtative
Distributive
- 15 + (7 + 6) = ( -15 + 7) + 6
The statement is an example of which of the following properties?
Identity
Associative
Inverse
Communtative
Distributive
The statement is an example of the Associative property, specifically the Associative property of addition. This property states that changing the grouping of numbers being added does not affect the sum. In this case, both sides of the equation have the same sum (8) because the grouping has changed.